Product design and development - Ulrich, Karl T.; Eppinger, Steven D. (New York : McGraw-Hill/Irwin, 2012)
"Treating such contemporary design and development issues as identifying customer needs, design for manufacturing, prototyping, and industrial design, Product Design and Development by Ulrich and Eppinger presents in a clear and detailed way a set of product development techniques aimed at bringing together the marketing, design, and manufacturing functions of the enterprise. The integrative methods in the book facilitate problem solving and decision making among people with different disciplinary perspectives, reflecting the current industry toward designing and developing products in cross-functional teams"--
"This book contains material developed for use in the interdisciplinary courses on product development that we teach. Participants in these courses include graduate students in engineering, industrial design students, and MBA students. While we aimed the book at interdisciplinary graduate-level audiences such as this, many faculty teaching graduate and undergraduate courses in engineering design have also found the material useful. Product Design and Development is also for practicing professionals. Indeed, we could not avoid writing for a professional audience because most of our students are themselves professionals who have worked either in product development or in closely related functions. This book blends the perspectives of marketing, design, and manufacturing into a single approach to product development. As a result, we provide students of all kinds with an appreciation for the realities of industrial practice and for the complex and essential roles played by the various members of product development teams. For industrial practitioners, in particular, we provide a set of product development methods that can be put into immediate practice on development projects"--
Machine generated contents note: Chapter 1 Introduction Chapter 2 Development Processes and Organizations Chapter 3 Opportunity Identification Chapter 4 Product Planning Chapter 5 Identifying Customer Needs Chapter 6 Product Specifications Chapter 7 Concept Generation Chapter 8 Concept Selection Chapter 9 Concept Testing Chapter 10 Product Architecture Chapter 11 Industrial Design Chapter 12 Design for Environment Chapter 13 Design for Manufacturing Chapter 14 Prototyping Chapter 15 Robust Design Chapter 16 Patents and Intellectual Property Chapter 17 Product Development Economics Chapter 18 Managing Projects.
Includes bibliographical references and index.
Keywords: Industrial management; Production management; Industrial engineering; New products -- Management